Respuesta :

Answer: (1,2)

Step-by-step explanation:

I will help you..

Given:

[tex]-2x-5y=-12\\10x-4y=2[/tex]

Lets cancel out the x term..

[tex]5(-2x-5y)=-12(5)\\=-10x-25y=-60[/tex]

Now our system looks like this:

[tex]-10x-25y=-60\\10x-4y=2[/tex]

Add.

[tex]-29y=-58\\y=2[/tex]

plug in 2 for y

[tex]-2x-5(2)=-12\\-2x-10=-12\\-2x=-2\\x=1[/tex]

Therefore the system is:

[tex](1, 2)[/tex]

If this helped consider marking brainiest.

Answer:

y=2 x=1

Step-by-step explanation:

1.        5(-2x-5y=-12)

10x-4y=2


2.         -10x-25y=-60
                    +

            10x-4y=2

3.            -29y=-60+2

              -29y=-58

                    y=2